Analisis Hukum Tentang Perlawanan Terhadap Putusan Verstek dalam Perkara Perdata di Indonesia - Fadlurrahman; Ilyas; Juhriati (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Verdict verstek is a decision rendered by a judge in a civil case when the defendant is absent without a valid reason at the first hearing even though it has been properly summoned. However, in practice, not a few defendants feel disadvantaged because they do not get a fair opportunity to defend themselves, so they file an opposition to the decision. This study aims to analyze the legal aspects of the mechanism of resistance to verstek decisions in civil cases in Indonesia, including the legal basis, requirements, procedures, and obstacles faced in its implementation. This research uses a normative juridical method with a statutory approach, and reviews several relevant court decisions. The results of the study show that opposition to a verdict is regulated in Article 124 HIR / Article 125 RBg which gives the defendant the right to file a verdict within 14 days of being notified of the verdict. Concretely, it was found that many challenges were rejected because they did not meet the deadline, were not supported by sufficient evidence, or because the reason for the defendant's absence was not considered valid by the court. In the judicial process, judges have an important role in conducting legal discovery and applying substantive justice through ex officio authority. Thus, the resulting decisions are not only oriented towards legal certainty, but also protect the welfare of the community and consider aspects of social needs. The Indonesian judicial system is expected to treat every justice seeker with respect and fairness as a whole human being through the verzet mechanism and the active role of judges.